The influence of motivation versus experience on recreation satisfaction: How appreciative- versus achievement-oriented recreation experience preferences relate to hunter satisfaction. (15th March 2019) - Schroeder, Susan A.; Cornicelli, Louis; Fulton, David C.; Merchant, Steven S.
Abstract: We present methods derived from customer satisfaction research that clarify factors influential to the satisfaction of recreation participants. We conducted mail surveys of Minnesota wild turkey hunters to explore differences between the explicit (i.e., stated) and implicit (i.e., derived from the relationship to satisfaction) importance of recreation experience preferences. Revised importance performance analysis, importance grid analysis, and penalty reward contrast analysis revealed differences between the explicit and implicit importance of recreation experiences and clarified how activity success may influence the relationship between experiences and satisfaction. We found some support for our hypothesis that experiences related to achievement (of goals for an activity) may more strongly relate to satisfaction than experiences related to appreciation (of nature) or affiliation (with family and friends). Our results emphasized the importance of activity-specific experiences over activity-general experiences for both successful and unsuccessful hunters and exposed a "motivation matching" process related to harvest success.